Not just a pathogen: The importance of recognizing genetic variability to mitigate a wildlife pandemic. (9th March 2021) - Azat, Claudio
Abstract : Emerging infectious diseases (EIDs) are increasingly recognized as a threat to both biodiversity and human health (Scheele et al., 2019; Wells et al., 2020). But pathogens cannot been seen as unique entities; their intraspecific genetic variability represented in variants, strains, antigenic types or genetic lineages may cause different impacts at the population level (Nelson and Holmes, 2007; Greenspan et al., 2018). The global spread of pathogens has been largely facilitated by globalization of transport, which particularly intensified during the last century (O'Hanlon et al., 2018). As seen with SARS‐CoV‐2, air travel can rapidly spread a pathogen globally (Wells et al., 2020). Furthermore, after initial introduction subsequent translocations of a pathogen may cause the contact of different variants facilitating the rise of novel genotypes that may have higher pathogenicity or transmissibility (Nelson and Holmes, 2007; Greenspan et al., 2018). Chytridiomycosis is an EID caused by the fungus Batrachochytrium dendrobatidis ( Bd ), that infects amphibian skin causing population declines to extinction in susceptible species. Now a wildlife pandemic, Bd has been recognized as the single pathogen causing the greatest loss of biodiversity on Earth (Scheele et al., 2019). Recent advances in genetics have made novel tools for pathogen detection and characterization more accessible and reliable (Boyle et al., 2004; Byrne et al., 2019). In this issue of Molecular Ecology Resources, Ghosh et al. (2021) report the development of a new genotyping qPCR assay targeting mitochondrial DNA (mtDNA) of Bd, and based on noninvasive swab samples (Figure 1), discriminate between the two most globally widespread and pathogenic genetic lineages of Bd . Having a better understanding of how the genetic diversity of a pathogen is distributed is crucial to understand their spread patterns and develop timely mitigation strategies.